Honestly evaluate staff goals to build professional development pathways. Issue 6 (22nd January 2018) - Sutton, Halley
Abstract : PHOENIX — How engaged are the workers in your office? That was the question Joellen Shendy, associate vice provost and university registrar at the University of Maryland University College; and Insiya Bream, assistant vice provost for registrar strategic operations at UMUC, sought to answer when they took a survey to determine professional engagement and goals.